Determining the Factors that Influence the Performance of Mts Teachers in Cirebon City - Rima Maulina; Lady Deviyada Sari; Ade Solahudin; Sunimah (Indonesian Journal of Business Analytics, 2025)
This research attempts to examine the impact of work-life balance, work environment, and teacher competence on the performance of MTs teachers in Cirebon City. The main focus of this research is for comprehension how work-life balance, work environment conditions, and the level of teacher competence can affect the quality of their performance. In the face of the ever-evolving dynamics of the world of education, understanding these factors is crucial for institutions to improve teaching effectiveness and support teacher professionalism in madrasah tsanawiyah. The approach taken in the investigation is a quantitative method through a causality approach, with data collected through questionnaires from respondents who are MTs teachers in Cirebon City. The results reveal that although work-life balance and work environment individually have no significant effect on teacher performance because they are used to adapting to the challenges of the profession, teacher competence remains a key factor in determining teaching effectiveness.  This study confirms that improving the competence of MTs teachers in Cirebon City is a major factor in raising their performance. It is advised that future studies investigate extra variables that affect teacher performance to raising the standard of the educational system in MTs in Cirebon City.